The Compensation Thesis vs the Mundell-Fleming Model in a fixed Exchange Rate Regime - Yan, Xue (Université d'Ottawa | University of Ottawa, 2004)
This paper seeks to look at an open economy in a fixed exchange system by virtue of comparing neoclassical view with post-Keynesian view as followed by former studies. In particular, it is critical to deploy the influential Mundell-Fleming (M-F) model and